Community Empowerment of KWT Rajawali for Economic and Food Security Enhancement through Aquaponic and Green Water Systems - Gumilang, Adi Surya Panji; Wilistanti, Mareta Gangsar; Yuristianti, Ranti Audina; Patra, Eka (Jurnal Abdimas Kartika Wijayakusuma, 2025)
The Rajawali Women Farmers Group (Kelompok Wanita Tani – KWT) is located in Ciomas Rahayu Village, where approximately 70% of the land area is occupied by residential housing. One of the efforts to optimize the remaining land for productive use is by integrating agriculture and aquaculture through an aquaponic system. This community service program focuses on enhancing the economic capacity and food security of KWT Rajawali, which initially generated an income of only IDR 410,000 from the sale of catfish (Clarias gariepinus) and water spinach (Ipomoea aquatica). The results of the program demonstrate that within the last three months, KWT Rajawali successfully increased its revenue to IDR 2,375,000 through the production and sale of catfish in yellow spice sauce, marketed via a pre-order system using the WhatsApp application. Furthermore, the mortality rate in catfish cultivation decreased significantly, from 30 fish per day to only 100 fish per harvest cycle. Similarly, the cultivation of water spinach yielded up to 3 kilograms per aquaponic pond using only half of the pond’s total capacity.